HYBRID MENTORING AS A POST-PANDEMIC HRD STRATEGY: EXAMINING ITS EFFECT ON EMPLOYEE COMPETENCY AND ADAPTIVE RESILIENCE - Fatwa Zuhanea (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The COVID-19 pandemic fundamentally transformed HRD practices, accelerating hybrid mentoring, a blended approach combining face-to-face and technology-mediated developmental interactions as a primary vehicle for employee competency development and resilience building. This study examines the effects of hybrid mentoring quality on employee competency and adaptive resilience in the post-pandemic healthcare sector in Banyumas Regency, Central Java, with employee competency as a mediating variable. Grounded in the Hybrid Sustainable Human Empowerment Framework (HSHEF; Zuhaena, 2026) and Social Learning Theory (Bandura, 1977), four hypotheses were tested using PLS-SEM with 131 healthcare workers from six Puskesmas and two district hospitals in Banyumas Regency. Results show that hybrid mentoring quality significantly affects employee competency (β = 0.452, p < 0.001) and adaptive resilience directly (β = 0.319, p < 0.001), employee competency significantly affects adaptive resilience (β = 0.394, p < 0.001), and employee competency partially mediates the mentoring-resilience relationship (indirect β = 0.178, p < 0.01). The model explains 64.1% of adaptive resilience variance (R² = 0.641). Findings provide evidence-based guidance for HRD practitioners designing hybrid mentoring programs in post-pandemic healthcare settings. Keywords: hybrid mentoring; employee competency; adaptive resilience; post-pandemic HRD; healthcare workers; HSHEF model; Banyumas